2008
DOI: 10.2151/sola.2008-009
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Water Vapor Mixing between the Atmospheric Boundary Layer and Free Atmosphere over Changwu, the Loess Plateau in China

Abstract: We investigated the diurnal variation of water vapor mixing between the atmospheric boundary layer (ABL) and the free atmosphere over the Loess Plateau in China. Water vapor and wind velocity in the troposphere were observed using a ground-based microwave radiometer and a wind profiler radar in 2005 and 2006. On sunny days in early summer, a strong vertical wind was generated in the afternoon followed by ABL development. Strong convection was enhanced when active cumulus convection developed in the afternoon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…By using a variety of PWV datasets, including the ECMWF and National Centers for Environmental Prediction reanalyses, GPS, radiosonde, and microwave satellite observations, the variability and trend in global PWV between 1979 and 2014 have been analyzed . The study showed positive global PWV trends for all five PWV datasets during three different periods: 1979-2014, 1992-2014, and 2000-2014. China, especially North China, is a typical region for studying water vapor feedback on global warming [33]. In order to strengthen understanding of climate change, it is necessary to analyze the PWV distribution and variations throughout North China in recent decades [34].…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…By using a variety of PWV datasets, including the ECMWF and National Centers for Environmental Prediction reanalyses, GPS, radiosonde, and microwave satellite observations, the variability and trend in global PWV between 1979 and 2014 have been analyzed . The study showed positive global PWV trends for all five PWV datasets during three different periods: 1979-2014, 1992-2014, and 2000-2014. China, especially North China, is a typical region for studying water vapor feedback on global warming [33]. In order to strengthen understanding of climate change, it is necessary to analyze the PWV distribution and variations throughout North China in recent decades [34].…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…The atmospheric flow with rainfall over China is significantly influenced by the East Asian summer monsoon (Li et al, ; Lu et al, ; Yang, Wang, et al, ). At the same time, China has undergone rapid economic growth with unfavorable meteorological conditions in recent decades, which has led to large emissions of aerosol and carbon dioxide (J. P. Guo et al, , ; Li et al, ; X. Y. Zhang et al, ; Yang, Wang, et al, , Yang, Zheng, et al, ), and thus these in turn induces rapid increases in temperature and inevitably changes the atmospheric water vapor due to the regional water vapor feedback effects resulting from climatic changes (Pan et al, ; Takahashi et al, ). However, current water vapor research remains at the case study level in certain local regions of China, and verification work on the accuracy of AIRS parameter inversions over China is scarce (Gui et al, ; Y. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to observe the exchange between ABL and FT, Takahashi et al investigated the diurnal variation of water vapor mixing between the ABL and FT over the Loess Plateau in China in 2005 and 2006 [45]. Vertical profiles of atmospheric water were measured from the ground-based microwave radiometry (MR) equipment, the time step was 1 min and the height was up to 10 km.…”
Section: Methods Of Ground-based Remote Sensingmentioning
confidence: 99%